2015
DOI: 10.1371/journal.pone.0138187
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dopaminergic VTA Neurons in General Anesthesia

Abstract: Recent studies have demonstrated that the central dopaminergic system is implicated in the mechanism underlying general anesthesia. Here, we investigated whether dopaminergic ventral tegmental area (VTA) neurons participate in general anesthesia. Dopaminergic VTA neurons were selectively ablated from male Sprague Dawley rats via the bilateral infusion of 6-hydroxydopamine (6-OHDA) into the VTA. Two weeks after infusion, the number of dopaminergic neurons in the bilateral VTA was markedly reduced in the 6-OHDA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 23 publications
(33 reference statements)
1
29
0
Order By: Relevance
“…We hypothesized that the regulation of the ventral reticular activation system after NB injury was impaired, which weakened the nerve projection of NB to a certain extent, and thus reduced the activity of FC neurons, i.e., the increase in the proportion of low-frequency high-delta band. The damage to the ventral tegmental dopaminergic neurons significantly increased propofol recovery time but did not change propofol sensitivity and induction time [22]. Just like our results, the sensitivity and induction time of propofol were not affected after NB injury, indicating that anesthesia recovery is not a reverse process of anesthesia induction.…”
supporting
confidence: 72%
“…We hypothesized that the regulation of the ventral reticular activation system after NB injury was impaired, which weakened the nerve projection of NB to a certain extent, and thus reduced the activity of FC neurons, i.e., the increase in the proportion of low-frequency high-delta band. The damage to the ventral tegmental dopaminergic neurons significantly increased propofol recovery time but did not change propofol sensitivity and induction time [22]. Just like our results, the sensitivity and induction time of propofol were not affected after NB injury, indicating that anesthesia recovery is not a reverse process of anesthesia induction.…”
supporting
confidence: 72%
“…A variety of experimental approaches have been used to study the neural circuits that underlie anesthetic-induced unconsciousness and recovery of consciousness in rodents, including designer receptors exclusively activated by designer drugs (DREADDs) (35), genetic manipulations (36), local and systemic drug administration (10,(37)(38)(39), microdialysis (40,41), targeted brain lesions (42,43), and electrical stimulation (34). Optogenetics is a novel tool that provides distinct advantages over previous techniques used to study anesthetic-induced unconsciousness and recovery of consciousness in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…One study in California mice found no effect of social defeat stress on D1 receptors in the only area examined, the NAcc (Campi, Greenberg, Kapoor, Ziegler, & Trainor, ). Dopamine neurons, and specifically D1 receptors (Taylor, Chemali, Brown, & Solt, ), are involved in the arousal from anesthesia (Zhou et al, ); and chronic stress can cause a reduction in dopamine transmission (Mizoguchi et al, ). It is thus theoretically possible that reduced dopamine transmission caused by the stress of anesthesia could result in an up‐regulation of D1 neurons.…”
Section: Discussionmentioning
confidence: 99%